THE ROLE OF NOTARIES IN PREVENTING MISAPPROPRIATION OF THE ESTABLISHMENT OF COOPERATION AGREEMENTS FOR THE UTILIZATION OF REGIONAL OWNED ASSETS - MAYENDRA, ENDRA; HIDAYATI, RAHMATUL (Awang Long Law Review, 2020)
A notary is a public official who is given the authority for attribution by Law to compose an authentic deed. The authority of a Notary is regulated in Article 15 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary, which contains all forms of actions, agreements, and provisions required by laws or those desired by the parties in the interest to be stipulated in an authentic deed. The intricacy is, what is the Notary's role in the cooperation agreement for the use of the regional asset to prevent misappropriation from the contract establishment process? The research method used is normative juridical, where the research emphasizes the use of legal norms in writing. The research results show that notaries play an important role in implementing the utilization of regional-owned assets, particularly within the scope of the Notary's authority, i.e., delivering the parties' wishes into a cooperation agreement deed appropriate to the form of utilization activities. Notaries can help create a government archiving system that is safe and structured. This form of support is in the form of a Notary Public, which will automatically become a party outside the government apparatus structure who participates in maintaining important local government documents; this is based on the mandate of Article 16 paragraph (1) letter (b) which states that Notaries must prepare deeds in the form of minuta deeds and store them as part of the Notary protocol. The conclusion is that the role of Notaries in utilizing a regional-owned asset requires Notaries to understand better and study the regulations governing the utilization agreement, as a Notary will face several problems in its implementation in formulating a cooperation agreement between local governments and the third parties. With the Notary's role in preventing misappropriation following the authority to establish contract deeds/authentic deeds, the Notaries can prevent legal problems in the deed establishment process.